2023
DOI: 10.1088/1402-4896/ad081f
|View full text |Cite
|
Sign up to set email alerts
|

Improvising CODAS method functionalized with grey numbers to improve the performance of PVD titanium carbon nitride (TiCN) thin film coating: a novel approach

Soham Das,
Partha Protim Das,
Ranjan Kr Ghadai
et al.

Abstract: This experimental study focuses on the deposition of TiCN thin film coating onto a bare p-type silicon substrate using physical vapor deposition (PVD) processes, with varying process parameters. The study employed a design of experiment in accordance with the L 16 orthogonal Array, followed by the implementation of the combinative distance-based assessment (CODAS) method functionalized with grey numbers to enhance the performance of the PVD process for the very first time in the film of thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…Overall, it is noticed that the pattern of the surface is even, and the deposited film is equally developed throughout the surface. The film deposited at higher deposition temperature (particularly at 950 and 1,000 °C) seems to be rougher as compared to other samples and similar results were also observed from AFM (Das et al, 2023a). It is also observed that at high temperature some agglomerated particles are form over the substrate.…”
Section: Morphological Analysis Using Atomic Force Microscopy (Afm)supporting
confidence: 79%
See 1 more Smart Citation
“…Overall, it is noticed that the pattern of the surface is even, and the deposited film is equally developed throughout the surface. The film deposited at higher deposition temperature (particularly at 950 and 1,000 °C) seems to be rougher as compared to other samples and similar results were also observed from AFM (Das et al, 2023a). It is also observed that at high temperature some agglomerated particles are form over the substrate.…”
Section: Morphological Analysis Using Atomic Force Microscopy (Afm)supporting
confidence: 79%
“…However further increase in temperature tends to increase the roughness of the film and the film deposited at 1,000 °C becomes rougher as compared to all the samples. The increase in roughness may be due to the increase of randomness of gas particles within the chamber at high temperature (Das et al, 2023a). The film thickness of the coating increased from 1.9 to 2.8 µm with increase of deposition temperature (Mwema et al, 2018).…”
Section: Morphological Analysis Using Atomic Force Microscopy (Afm)mentioning
confidence: 99%